Aplikasi Digital Pencegahan Covid-19 dan Penghormatan terhadap Hak Asasi Manusia - Ika Cahyo Purnomo; Anggraeni Endah Kusumaningrum (Pusat Riset dan Inovasi Nasional, 2022)
COVID-19 containment apps have raised a new hope in dealing with COVID-19 in various countries. Automatic contact tracing capabilities combined with various other transmission prevention functions have yielded favorable outcomes in controlling outbreaks. Although its nature seems promising, the use of this type of application also saves the potential for human rights violations. The risk is related to the increasingly widespread functionality of the application, the restrictions of personal freedom, the potential breach of privacy, and the possibility of marginalizing people who cannot access the application. This paper describes how this application works in general, how it can affect respect for human rights, and then analyzes incidents that have the potential to violate human rights related to the use of the application to further provide some potential solutions on how the application can still be utilized with a minimum threat to individual rights.